A comprehensive analysis of heavy metal contamination in soil and water across various soil types - Wan Sulaiman, Wan Syibrah Hanisah; Mohd Latiff, Nur Hanie (Nova Science Publishers, 2024)
Heavy metals, which originate from either natural sources or anthropogenic sources, are widely-recognized environmental contaminants due to their toxicity, persistence, and capacity for bio accumulation. The extraction of mineral resources through mining and industrial processing and the subsequent use of those resources for industrial, agricultural, and economic development have increased the mobilization of these elements in the environment, and at the same time disrupted their biogeochemical cycles. This chapter aims to present the different types of heavy metal contamination and their transport, water quality and soil analyses, as well as the impacts on living organisms in natural water, sediments, and soil. Considering the issue, it is crucial to measure and extensively document the potentially harmful heavy metals in natural water bodies, sediments, and soils caused by human activities. A thorough review of the heavy metals contamination could provide useful insights in reducing the ecological risks related to the effects of these contaminants on both human and health, and thus to gain more understanding on the bioaccumulation process of heavy metals contamination.